Reading and Oral Language Skills in Children With Developmental Language Disorder: Influence of Socioeconomic, Educational, and Family Variables - Lara-Díaz, María Fernanda; Mateus-Moreno, Angélica; Beltrán-Rojas, Judy Costanza (Frontiers in Psychology, 2021)
The Developmental Language Disorder (DLD) is a delay in language skills that cannot be explained by sensory or cognitive difficulties. Currently, there are limited studies that analyze how socioeconomic, educational, and family variables influence reading skills of Spanish-speaking children with DLD at school. This study identifies how oral language performance and reading skills of children with DLD are linked to socioeconomic, educational, and family factors. Oral language, phonological awareness and reading abilities were assessed in a sample of 15 children diagnosed with DLD and their controls by age and gender. Children's parents answered a Likert scale questionnaire inquiring about some aspects related to the family's socioeconomic status, mothers' educational level, family support, academic average, and repetition of school years of the participants. The results indicate that children with DLD have a lower performance in phonological awareness tasks as well as in reading abilities. There is also a direct relationship between their performance in language and reading skills and variables as mother's educational level and family support. Likewise, children in the sample have a lower academic average as well as a higher school year repetition rate interfering in their academic life. Educational implications of these findings and a discussion on possible causality axes and protective factors that contributes to support this population are presented.